Effect of water content on correlation of biomechanical properties and grayscale of articular cartilage using low-field MRI - Abd. Latif, Mohd Juzaila; Zakaria, Mohamad Shukri; Hamshary, Furas Anes Saleh; Harun, Muhamad Noor; Mahmud, Jamaluddin; Nguyen, Ho Quang (Universiti Malaysia Perlis, 2022)
The early assessment of osteoarthritis is very crucial since articular cartilage has a very limited ability to regenerate and self-repair as the degeneration happened. Thus, MRI is the most important imaging modality for cartilage evaluation among all the other methods used to diagnose osteoarthritis. However, the cartilage image obtain from low-field MRI is still uncertain particularly in quantitative assessment. Hence this study aims to determine the effect of dehydration on the correlation between grayscale MRI image and biomechanical properties of articular cartilage. In this study, the cartilage specimens were obtained from bovine femoral head which were dehydrate in stages in terms of time expose to room temperature. The specimens were then scanned at every dehydration stage using 0.2 T MRI to obtain the cartilage image and characterized the image based on the grayscale’s intensity. Subsequently, indentation test was conducted on specimens at every dehydration level to determine the cartilage biphasic properties of elastic modulus and permeability. The finding showed that the grayscale of cartilage had a moderate correlation with the cartilage biphasic elastic modulus and permeability. More importantly the low-field MRI was able to indicate the high rate of articular cartilage ability to loss its water content.